Surgical Treatment Of Pendred Syndrome With Thyroid Nodule: A Case Report - Ferianto, Djonny; Syamsu, Salman Ardi; Sapan, Vannes Caesar Palebangan; Indra; Sampepajung, Elridho; Pieter Jr, John (Faculty of Medicine, Hasanuddin University., 2024)
Introduction and importance: Pendred syndrome (PS) is a genetic disease inherited in an autosomal recessive pattern. In PS patients, the ability of thyroid gland to accumulate iodide in the follicle lumen is disrupted, causing insufficient thyroid hormone synthesis and goiter to occur as compensation. However, this symptom does not often appear, as goiter is only detected in 30–75% of PS patients. Presentation of case: A 33-year-old Buginese man complained of a painless mass in the neck. In the past 3 months, the mass has shown rapid growth, followed by symptoms of agitation, irritability, and hyperhidrosis. The patient was previously diagnosed with nodular goiter and was taking Levothyroxine. Furthermore, there was a history of the same disease in the patient’s grandmother and younger sibling. Physical examination showed grade III goiter (WHO criteria) with hard consistency and no palpable nodules. Laboratory tests showed routine blood tests, kidney and liver function in normal limits, 1.14 ng/dL FT4, free triiodothyronine level of 6.07 pg/dL, and 2,401 mIU/L TSH level. Chest X-ray results showed tracheal narrowing at the level of the superior thoracic aperture. Similarly, thyroid USG showed that the size of the right lobe was enlarged and anechoic. CT (Computerized Tomography) scan of the cervix showed diffuse enlargement in each lobe and the patient was diagnosed with PS. Right isthmolobectomy and thyroid biopsy were carried out and pathological anatomical examination results showed thyroid follicular nodular disease with cystic degeneration. After surgery, thyroxine hormone replacement therapy was continued. Discussion: Surgical intervention strategies may be employed to inhibit the advancement of disease and mitigate thyroid enlargement, consequently decreasing the likelihood of obstruction and malignancy. Conclusions: In cases of PS with large thyroid nodules pressing on the trachea, isthmolobectomy was carried out to obtain good results and no recurrence.